Actions of cofinite groups on cofinite graphs. Issue 1 (2nd January 2020) - Acharyya, Amrita; Das, Bikash
Abstract: We defined group actions on cofinite graphs to characterize a unique way of uniformly topologizing an abstract group with profinite topology, induced by the cofinite graphs, so that the aforesaid action becomes uniformly equicontinuous.